Analisis Kekuatan Struktur Komposit Sandwich Pada Main Landing Gear UAV : Strength Analysis of Sandwich Composite Structures Main Landing Gear UAV - Jauharul Akfiya sudjaelan; Sahril Afandi; Endah Yuniarti (FTK UNSURYA, 2023)
Tricycle landing gear is a landing gear configuration on an aircraft with nose landing and main landing. Strength analysis of sandwich composites with impact loads aims to determine the maximum strength that can be resisted by sandwiches with several layers of lamina arranged with variations orientation fiber to obtain stiffness, to determine the type of damage caused by excessive loading. Fiber direction optimization was carried out to obtain optimal fiber direction variations in receiving loading, the optimal fiber direction was [(0)(45)(-45)(90)(0)]s with a significant Tsai-hill value from 0.091052752 to 0.057597845 after optimization. Simulation of impact loading with vertical velocity variations of 2 m/s, 3 m/s 4 m/s, 6 m/s, 8 m/s, 10 m/s, 12 m/s, 15 m/s using the finite element method by utilizing the Abaqus CAE software on the tricycle landing gear model and conducting tests to obtain large displacem ents, stresses and strains. By doing the test, it is found that the main landing gear structure is able to withstand a landing speed of up to 12 m/s with a large X-axis stress (S11) of 447.118 Mpa, a Y-axis stress (S22) 30.4995 Mpa, a shear stress of 26.2218 Mpa with a large a displacement of 11.9461 mm and a tsai-hill value of 0.5920. At a landing speed of 15 m/s the landing gear structure fails with a tsai-hill value that has passed the failure index 1, with a large X-axis stress (S11) 477.556 mpa, Y-axis stress (S22) 44.4075 Mpa, shear stress of 35 .2047 Mpa with a large displacement of 15.8297 mm and a tsai-hill value of 1.1336 where the landing speed of this landing gear structure failed, indicated by the tsai-hill value which had exceeded the failure index value 1. Keywords: Main Landing Gear, UAV, Drop Impact, CompositeSandwich.